2005
DOI: 10.1897/04-157r.1
|View full text |Cite
|
Sign up to set email alerts
|

Early–life‐stage toxicity in offspring from exposed parent medaka, Oryzias latipes, to mixtures of tributyltin and polychlorinated biphenyls

Abstract: The present study examined the effects of tributyltin (TBT), polychlorinated biphenyls (PCBs), and mixtures of both chemicals on reproduction in Japanese medaka, Oryzias latipes. For 21 d we gave groups of medaka freeze-dried brine shrimp flakes contaminated with a mixture of either 0, 1, 5, or 25 microg TBT g(-1) plus 0 or 25 .micro PCBs g(-1). We measured the fecundity and fertility of the parent fish and assessed the deformity, hatchability, time-to-hatching, and swim-up failure rate of the next generation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Moreover, environmentally contaminated parent fish and consequently the eggs are exposed to complex mixtures of toxicants. Recent research with the Japanese medaka (Oryzias laptipes) showed for instance that parental exposure to a combination of PCB and TBT has a more adverse effect on the embryonic development than the added effect of the individual substances (Nakayama et al, 2005).…”
Section: Field Relevancementioning
confidence: 99%
“…Moreover, environmentally contaminated parent fish and consequently the eggs are exposed to complex mixtures of toxicants. Recent research with the Japanese medaka (Oryzias laptipes) showed for instance that parental exposure to a combination of PCB and TBT has a more adverse effect on the embryonic development than the added effect of the individual substances (Nakayama et al, 2005).…”
Section: Field Relevancementioning
confidence: 99%
“…Also, TBT and TPT can inhibit reproduction (14,15). Therefore, in the present study, the following questions were addressed.…”
mentioning
confidence: 96%
“…Ocular and morphological malformations have been observed in embryos and larvae of European minnows (Phoxinus phoxinus) and zebrafish (Danio rerio) after in ovo exposure of TPT (12,13) and in the offspring of medaka (Oryzias latipes) maternally exposed to TBT and TPT (14,15). Also, TBT and TPT can inhibit reproduction (14,15).…”
mentioning
confidence: 99%
“…Thus, there is evidence that TBT may affect the neuroendocrine system of fish. We previously reported that TBT impaired reproduction of medaka and suppressed sexual behavior of males (Nakayama et al, 2004a(Nakayama et al, , 2005. These results suggest that reduced 5-HT and DA in TBT-exposed medaka could disrupt secretion of GnRH or GTH and consequently induce reproductive impairment and suppression of sexual behavior.…”
Section: Discussionmentioning
confidence: 83%